2016
DOI: 10.1007/s00464-016-4751-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis after endoscopic submucosal dissection for early gastric cancer in super-elderly patients

Abstract: ESD was performed safely, and death related to gastric cancer was prevented in super-elderly patients with comorbidities, regardless of the degree of the disease. However, patients with comorbidities are at a high risk of poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 40 publications
2
41
1
Order By: Relevance
“…Regarding long‐term outcomes, the main cause of death was other‐organ malignancy in patients who underwent ESD for EGC. Yoshifuku et al . reported that the main cause of death in patients aged ≥85 years who underwent ESD for EGC was pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding long‐term outcomes, the main cause of death was other‐organ malignancy in patients who underwent ESD for EGC. Yoshifuku et al . reported that the main cause of death in patients aged ≥85 years who underwent ESD for EGC was pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The mean life expectancy in Japan at the age of 85 years was reported to be 6 and 8 years for men and women, respectively . Although previous studies have reported that endoscopic resection of EGC can be carried out safely even in older patients, resection has not been shown to improve the prognosis of older patients . Therefore, as shown by the present patient, no treatment might be the appropriate strategy.…”
mentioning
confidence: 95%
“…Those aged more than 75 years accounted for 12.3% of the Japanese population as of 2013, and this is expected to reach 27% by 2060 (13). More importantly, the super-elderly population (aged more than 85 years) increased from 1.4 to 4.8 million during the last two decades (14). As our aging society advances, super elderly people with gastric cancer have increased annually.…”
mentioning
confidence: 99%
“…As our aging society advances, super elderly people with gastric cancer have increased annually. Opportunities to perform ESD for EGC in super elderly patients have surely increased (14). Compared to surgical intervention, ESD is less invasive, and it improves their quality of life preserving gastric function.…”
mentioning
confidence: 99%
See 1 more Smart Citation